(untitled) (Global Journal of Management and Business Research, 2021)
Abstract- Contingency planning denotes the overall planning preparation for any firm to meet unexpected events at any time to avoid losses from any human-made or natural or technological catastrophe. In the event of Covid-19, contingency planning requirement is a demanding issue. The planning helps to Identify the activities, resources, and procedures needed to carry out the bank’s data processing requirements. In the pandemic, Banks need to assign responsibilities to designated personnel and provide guidance for recovering during prolonged periods of interruption to normal operations and ensure co-ordination with other staff who will participate in the contingency.